2009
DOI: 10.1080/03670240802577390
|View full text |Cite
|
Sign up to set email alerts
|

Level of Adherence to the Mediterranean Diet Among Elderly Individuals Living in Mediterranean Islands: Nutritional Report from the Medis Study

Abstract: The level of adherence to the traditional Mediterranean diet was moderate. People living in rural areas seem to better hold these traditional dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…Recent studies in European countries in particular have shown strong evidence that the Mediterranean dietary pattern, observed in some Mediterranean countries in the 1950s and 1960s, has changed to a more "westernized" type of diet at all ages [26,27]. In Greece, where this traditional dietary pattern was first observed after the Second World War, evidence suggests that the eating habits of young, middle-aged and elderly have changed to a more "westernized" pattern [28]. This change is mainly visible in areas of fast urbanization and economic development, where obesity is a major problem [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in European countries in particular have shown strong evidence that the Mediterranean dietary pattern, observed in some Mediterranean countries in the 1950s and 1960s, has changed to a more "westernized" type of diet at all ages [26,27]. In Greece, where this traditional dietary pattern was first observed after the Second World War, evidence suggests that the eating habits of young, middle-aged and elderly have changed to a more "westernized" pattern [28]. This change is mainly visible in areas of fast urbanization and economic development, where obesity is a major problem [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Islands Study (MEDIS) examined bioclinical, lifestyle, behavioral, and dietary characteristics in a sample of elderly people living in the Mediterranean Islands 21. MEDIS is a health and nutrition survey where a random, population-based, multistage sampling method was used to select 1,190 men and women (>65 years) from the Republic of Cyprus and the following Greek islands: Mitilini, Samothraki, Cephalonia, Crete, Limnos, Corfu, and Zakynthos.…”
Section: A Summary Of Observational/epidemiologic Studiesmentioning
confidence: 99%
“…Only few studies have been designed to explore the factors associated with the adherence to the Mediterranean diet specifically in the aforementioned areas, such as the Mediterranean islands [11,12] and even less interested young populations [13,14,15]. Some studies also emphasized the role of the environment ( i.e.…”
Section: Introductionmentioning
confidence: 99%